Assistance for Florida's Rural Communities: The Florida Resource Directory - David Mulkey; Henry Cothran (EDIS)
Local communities, as well as organizations and businesses within those communities, often need information about the types of assistance programs available through state and federal government. In response to this need in Florida, the Governor's Office of Trade, Tourism, and Economic Development maintains the Florida Resource Directory. This is EDIS document FE425, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published August 2003.